1978
DOI: 10.1051/rphysap:019780013012071900
|View full text |Cite
|
Sign up to set email alerts
|

Shot noise behaviour of subthreshold MOS transistors

Abstract: It is shown that assuming weak inversion, low drain current asymptotic value of the gate equivalent noise resistor is given by n2/2 UT/ID, corresponding to shot noise. Measurements confirming this theory as well as flicker noise measurements on n and p channel transistors integrated with either bulk or SOS CMOS silicon gate technology are presented

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 5 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Pulses therefore occur at the modulation frequency and not at its submultiple as in a previous experiment. 3 Display on a sampling oscilloscope confirms this.…”
mentioning
confidence: 60%
“…Pulses therefore occur at the modulation frequency and not at its submultiple as in a previous experiment. 3 Display on a sampling oscilloscope confirms this.…”
mentioning
confidence: 60%
“…The device that synthesizes the resistance R dc deserves careful attention for what concerns its generated noise ͑in particular, for the shot noise component 16,17 ͒ and its parasitic capacitances to minimize the noise generated by the amplifier, as will be discussed in the Sec. By doing this, no limitation will be encountered in integrating it in a standard complementary metal-oxide-semiconductor ͑CMOS͒ technology.…”
Section: DC Path Designmentioning
confidence: 99%
“…In the saturation region, the most prevalent region for TL circuits, and simplifies to [39]. In addition to this white shot noise, the MOS transistor also exhibits noise.…”
Section: B Mos Transistormentioning
confidence: 99%
“…In addition to this white shot noise, the MOS transistor also exhibits noise. However, it can be shown that noise is negligible at low current levels [39], the region used in MOS-TL circuits.…”
Section: B Mos Transistormentioning
confidence: 99%
See 1 more Smart Citation